Hierarchical hybrid nanostructures of Sn3O4 on N doped TiO2 nanotubes with enhanced photocatalytic performance1. Issue 37 (7th October 2015) - Yu, Xin; Wang, Longfei; Zhang, Jian; Guo, Weibo; Zhao, Zhenhuan; Qin, Yong; Mou, Xiaoning; Li, Aixue; Liu, Hong
<x xml:space="preserve">Abstract</x> Sn3O4/N-TiO2 hierarchical hybrid nanostructures exhibit enhanced photocatalytic activity in the decomposition of MO and promote hydrogen evolution from water.